PEDAGOGICAL SKILLS IN PROMOTING ENGLISH AMONG YOUNG PEOPLE (Multidisciplinary Journal of Science and Technology, 2024)
This article examines key pedagogical skills for promoting English learning among young people, including effective communication, classroom management, and innovative teaching methods. It highlights the importance of cultural awareness and technology integration in engaging students and enhancing language acquisition, helping them achieve success in both academic and professional settings.